2024
DOI: 10.1136/bjsports-2023-107598
|View full text |Cite
|
Sign up to set email alerts
|

Contexts, behavioural mechanisms and outcomes to optimise therapeutic exercise prescription for persistent low back pain: a realist review

Lianne Wood,
Nadine E Foster,
Sarah Gerard Dean
et al.

Abstract: ObjectiveTherapeutic exercises are a core treatment for low back pain (LBP), but it is uncertain how rehabilitative exercise facilitates change in outcomes. Realist reviews explore how the context (C) of certain settings or populations and underlying mechanisms (M) create intended or unintended outcomes (O). Our objective was to explore and understand the behavioural mechanisms by which therapeutic exercise creates change in outcomes of adherence, engagement and clinical outcomes for patients with LBP.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 135 publications
(379 reference statements)
0
2
0
Order By: Relevance
“…Our team undertook a realist review to answer the question: 'How does therapeutic exercise prescription create change in outcomes of importance for patients with persistent LBP?' (Wood et al, 2024). We found that engagement, adherence to and outcomes following therapeutic exercise prescription are optimised when the mechanisms of trust, motivation and confidence are utilised.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our team undertook a realist review to answer the question: 'How does therapeutic exercise prescription create change in outcomes of importance for patients with persistent LBP?' (Wood et al, 2024). We found that engagement, adherence to and outcomes following therapeutic exercise prescription are optimised when the mechanisms of trust, motivation and confidence are utilised.…”
Section: Introductionmentioning
confidence: 86%
“…The content of each module was co-designed according to learning outcomes. We used input from the [blinded] design team to ensure that the programme theory identified within the realist review (Wood et al, 2024) was presented in an optimal format and met the quality assurance framework for learners needs.…”
Section: Online Training Programmementioning
confidence: 99%